Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT Angkasa Pura Support - Asyifa, Haana; Siska, Elmira; Indra, Natal (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine how much influence work motivation and work environment have on employee performance at PT Angkasa Pura Support at the head office. The research method used is a quantitative method approach with data collection techniques using probability sampling with a population of 178 employees and samples taken using the slovin formula, namely as many as 65 respondents. Data collection using a questionnaire in Likert scale units. Data processing uses SPSS 16 software for instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that partially, work motivation or work environment has a positive and significant relationship to employee performance. Likewise, simultaneous testing of both motivational and work environment variables has a positive and significant relationship to the performance of employees of PT Angkasa Pura Support.